Mexican messiah : Andrés Manuel López Obrador - Grayson, George W., 1938-2015 (Pennsylvania State University Press, 2007)
"The emergence of Latin American firebrands who champion the cause of the masses and rail against the evils of neoliberalism and Yankee imperialism - Hugo Chavez in Venezuela, Evo Morales in Bolivia, Nestor Kirchner in Argentina, Andres Manuel Lopez Obrador in Mexico - has changed the landscape of the Americas in dramatic ways. This will be the first biography to appear in English about one of these charismatic figures, who is known in his country by his adopted nickname of "the Little Ray of Hope."" "The book follows Lopez Obrador's life from his early years in the flyspecked state of Tabasco, his university studies, and the period that he lived among the impoverished Chontal Indians. Even as he showed an increasingly messianic elan to uplift the downtrodden, he confronted the muscular Institutional Revolutionary Party (PRI) in running twice for governor of his home state and helping found the leftist-nationalist Democratic Revolutionary Party (PRD). As the PRD's national president, he escalated his political and ideological warfare against his former president, Carlos Salinas, and other "conspirators" determined to link Mexico to the global economy at the expense of the poor. His strident advocacy of the "have nots" lifted Lopez Obrador to the mayorship of Mexico City, which he rechristened the "City of Hope." Its ubiquitous crime, traffic, pollution, and housing problems have made the capital a tomb for most politicians. Not for Lopez Obrador. Through splashy public works, monthly stipends to senior citizens, huge marches, and a dawn-to-dusk work schedule, he converted the position into a trampoline to the presidency." "Although he lost the official count by an eyelash, the hard-charging Tabascan cried fraud, took the oath as the nation's "legitimate president," and barnstormed the country, excoriating the "fascist" policies of President Felipe Calderon and preparing to redeem the destitute in the 2012 presidential contest."